Eficiência dos agricultores familiares beneficiados com créditos do programa de reforma agrária e do PRONAF para assentamentos: análise comparativa em um estudo de caso. - Sousa Junior, José Luís de (2007)
The present work has as general objective, to verify the impact of the Credits of Installation of the National Program of Agrarian Reform and of the PRONAF-A (Programs National of Invigoration of the Family Agriculture - A group) on the rural workers' of the Assentamento Santa Rita income mainly in the municipal district of High - Piauí. For so much, it was made a discussion on rural poverty, family agriculture in Brazil and considerations on lines of credit of PRONAF, being discussed, also, on the establishments of agrarian reform in Brazil. Soon after, a general analysis of the characteristics of the Assentamento Santa Rita was elaborated and it was made a statistical analysis, growing tests of hypotheses, to verify the impact of the referred credits of the Programs in Santa Rita, considering the variables income medium mainly, the cultivated area, the years of study of the boss of the family and of the number of members of the family, for the years of 2001 and 2005. Besides, it was made the comparison of the averages amostrais of each variable above mentioned, considering the samples of data of Santa Rita, PNAD and PRONAF-HER for every year of reference. The base of data for the analysis it was collected in INCRA/PI (National Institute of Colonization and it Reforms Agrarian of Piauí), CEPAC (Center Piauiense of Cultural Action) of PNAD (Researches National for Sample of Homes) of IBGE. The results show that in Santa Rita families that had support of credits of the Programs referency reside, tends, at the level of 5% of statistical significancy, the income medium monthly domiciliar grew from 2001 to 2005.